2018
DOI: 10.3389/fphys.2018.00802
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretch Negatively Regulates IL-1β Secretion Through the Inhibition of NLRP3 Inflammasome Activation by Attenuating the AMP Kinase Pathway

Abstract: Macrophages are immune cells of hematopoietic origin that play diverse roles in host defenses and tissue homeostasis. In mechanical microenvironments, macrophages receive mechanical signals that regulate various cellular functions. However, the mechanisms by which mechanical signals influence the phenotype and function of macrophages in the process of inflammation have not yet been elucidated in detail. We herein examined the effects of cyclic stretch (CS) on NLR family, pyrin domain-containing 3 (NLRP3) infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Therefore, the relationship between mechanical stress and inflammasome signaling is still unclear. Recently, we found that cyclic stretch suppresses the NLRP3 inflammasome in macrophages [51] and will introduce our new findings in the latter part of this paper (Fig. 2).…”
Section: Relationship Between Mechanical Stress and The Nlrp3 Inflammmentioning
confidence: 63%
“…Therefore, the relationship between mechanical stress and inflammasome signaling is still unclear. Recently, we found that cyclic stretch suppresses the NLRP3 inflammasome in macrophages [51] and will introduce our new findings in the latter part of this paper (Fig. 2).…”
Section: Relationship Between Mechanical Stress and The Nlrp3 Inflammmentioning
confidence: 63%
“…In the present study, we demonstrated for the first time that cyclic stretch induced PDL cells to secrete exosomes, which exhibited anti-inflammatory properties in macrophages. We previously reported that the exposure of LPS-primed macrophages to cyclic stretch inhibited IL-1β secretion by attenuating the AMP kinase pathway (45). Therefore, the NLRP3 inflammasomes of macrophages may be tightly regulated by multiple feedback systems that maintain immune/inflammatory homeostasis in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the resistance of gastrocnemius muscle of clodronate liposome-administered mice to hindlimb immobilization ( Figure 3A-C), mechanosensory function of macrophages recruited from circulating blood appears to be involved in tissue homeostasis. Whereas the decrease in MCP-1 expression in cultured macrophages by FSS relates to anti-inflammation, both pro-and anti-inflammatory effects of cyclical stretching of cultured macrophages have been reported [46,47]. Such variation might be due to the complexity of cyclical stretching, which is a combination of stretching and relaxation that can affect cellular signaling in opposite directions [48].…”
Section: Discussionmentioning
confidence: 99%